2018
DOI: 10.1038/s41386-018-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term high-fat food or methamphetamine intake and serotonin 2C receptors on reversal learning in female rhesus macaques

Abstract: Perseverative behavior has been highly implicated in addiction. Activation of serotonin 2C receptors (5-HTRs) attenuates cocaine and high caloric food intake, but whether a 5-HTR agonist can reduce high caloric diet (HCD) or methamphetamine (METH) intake and response perseveration remains unknown. Clarifying the role of 5-HTRs in these behaviors will improve knowledge of neurochemical processes that regulate flexible decision-making and whether improvements in decision-making are accompanied by decreases in HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Moreover, this apparent opposite effect of WAY163909 administration, decreasing impulsivity in the SSRTT and increasing feeding, may be a result of effects of 5-HT 2C R agonism in different parts of the brain with distinct dissociable functions on behaviour. However, a recent study (35) has demonstrated that agonism of the 5-HT 2C R with WAY163909, affected response control, akin to the improved stopping we have found here, in combination with consumption of a high calorific diet suggesting a relationship between dietary habits and decision-making strategies with 5-HT 2C R at the nexus (36,37).…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, this apparent opposite effect of WAY163909 administration, decreasing impulsivity in the SSRTT and increasing feeding, may be a result of effects of 5-HT 2C R agonism in different parts of the brain with distinct dissociable functions on behaviour. However, a recent study (35) has demonstrated that agonism of the 5-HT 2C R with WAY163909, affected response control, akin to the improved stopping we have found here, in combination with consumption of a high calorific diet suggesting a relationship between dietary habits and decision-making strategies with 5-HT 2C R at the nexus (36,37).…”
Section: Discussionsupporting
confidence: 55%
“…These brain regions comprise the mesolimbic dopamine reward pathway that has been implicated in substance abuse, overeating of high caloric foods, and perseverative impairments during discrimination reversal learning procedures [3,7]. Perez Diaz et al [4] extend these previous findings by suggesting that 5-HT 2C activation attenuates methamphetamine-related and high caloric dietrelated increases in perseverative responding in a discrimination reversal learning procedure.…”
mentioning
confidence: 84%
“…Although the findings from Perez Diaz et al [4] are provocative, the results prompt several questions like any good experiment does. Three will be mentioned.…”
mentioning
confidence: 90%
See 2 more Smart Citations